THEORETICAL ISSUES OF INNOVATIVE DEVELOPMENT OF SMALL BUSINESS - Akbarov Bakhodir Makhamadolimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article reveals the nature of theoretical issues on the innovative development of small business and presents the ways of sustainable development of small business during the crises observed in the country's economy.